Effectiveness of a home-based computerized cognitive training in Parkinson's disease: a pilot randomized cross-over study - Tagliente, Serena; Minafra, Brigida; Aresta, Simona; Santacesaria, Paola; Buccoliero, Andrea; Palmirotta, Cinzia; Lagravinese, Gianvito; Mongelli, Davide; Gelao, Christian; Macchitella, Luigi; Pazzi, Stefania; Scrutinio, Domenico; et al. (Frontiers in Psychology, 2025)
IntroductionCognitive symptoms are common in Parkinson's Disease (PD), and digital interventions like telerehabilitation other an accessible way to manage these symptoms. This study aimed to assess the effectiveness of a Home-Based Computerized Cognitive Training (HB-CCT) program in individuals with PD using a pilot randomized cross-over design.MethodsTwenty-five participants (mean age 69.32 ± 7.21 years, mean MDS-UPDRS III 33.76 ± 14.25) with PD and mild cognitive impairment were enrolled. They underwent neuropsychological assessments at three time points (5-week intervals): Baseline, after the HB-CCTi, and after Standard Care. The HB-CCT consisted of the Neurotablet® platform that was used to target cognitive domains such as Attention, Memory, Perception, Executive Functioning and Language. All participants completed both the Neurotablet intervention and Standard Care blocks in a randomized order. After a Shapiro-Wilk test, non-parametric repeated measures analyses of variance (Friedman's test) and post-hoc comparisons corrected with the Benjamini-Hochberg approach were performed to compare the effects on primary and secondary cognitive outcomes over experimental intervention and Standard Care.ResultsThe results from the Friedman analysis revealed significant improvements in Word List Immediate Recall, Digit Span Forward and Complex Figure Recall (all p < 0.001) following the HB-CCT, compared to the Baseline. Additionally, Naming performance showed significant improvement after the HB-CCT (p = 0.02). Significant differences were also observed when comparing the HB-CCT with Standard Care, with improved performance in TMT-A (p = 0.02), Phonemic Fluency (p < 0.01), and Digit Span Forward (p < 0.01).DiscussionThese findings suggest that HB-CCT via Neurotablet can effectively enhance specific cognitive abilities in PD, supporting the role of digital, home-based interventions as feasible strategies to mitigate cognitive decline.